Designing Product Labels and Digital Marketing as Branding Strategies for Yu Marni’s Tiwul Product - Nopita, Dewi; Rodhiyah Mardhiyyah; Maya Listiyani; Tegar Julianto (Jurnal Internasional Teknik, Teknologi dan Ilmu Pengetahuan Alam, 2023)
Yu Marni is a culinary SME undertaking unique local food of Gunungkidul, Yogyakarta with a wide variety of products, including instant tiwul, tiwul flour, corn rice, gatot, and several other products. The packaging designs of these products lacking complete information such as the name of the product and how to use the product. Product marketing is done by entrusting their products to several souvenir shops and utilizing social media such as WhatsApp and Instagram. To make it easier for consumers to find information on Yu Marni's products, a packaging design was created that contained information including the logo, brand, product name, packaging theme, and other supporting information. In addition, a website is created to enhance products introduction to the public as well as a means to perform modern transactions. The rebranding activity resulted in a product packaging design that contained information about the identity of the company and its products. The website that was built is not only for product promotion, but can also be used for transactions and transaction data recap. Keywords: Instant tiwul, Labeling, Marketing, Product Image, Rebranding.